2017
DOI: 10.1021/acs.jpcc.7b08170
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Substrate-Induced Strain of As-Grown Graphene on Cu(100) Using Temperature-Dependent Raman Spectroscopy: Estimating the Mode Grüneisen Parameter with Temperature

Abstract: The strategy of using the thermal expansion of a copper single crystal can provide an approach to produce homogeneous strain along the basal plane to study the strain characteristic of graphene with temperature. Using an in situ Raman measurement under an ultrahigh vacuum (UHV) environment, the ability to remove contaminations allowed the direct observation of the strain property in as-grown chemical vapor deposited graphene (CVD-graphene) with temperature on a Cu(100) substrate. In this study, the strain coef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 67 publications
0
15
0
Order By: Relevance
“…The frequencies of the two major Raman peaks in graphene (G and G' peaks) and in MoS2 (E' and A' peaks) are influenced by charge transfer doping and strain, and correlation analysis between the two modes offers a way to decouple their effects. [15][16][17][18][19][20][21][22] That is, by plotting the frequencies of the G' (E') band against the G (A') band in graphene (MoS2), one can establish the extent of strain versus doping in each layer. In addition to Raman peaks, monolayer MoS2 exhibits strain-and dopingdependent photoluminescence (PL) emission, offering an additional means to study the interaction between graphene and MoS2.…”
Section: Introductionmentioning
confidence: 99%
“…The frequencies of the two major Raman peaks in graphene (G and G' peaks) and in MoS2 (E' and A' peaks) are influenced by charge transfer doping and strain, and correlation analysis between the two modes offers a way to decouple their effects. [15][16][17][18][19][20][21][22] That is, by plotting the frequencies of the G' (E') band against the G (A') band in graphene (MoS2), one can establish the extent of strain versus doping in each layer. In addition to Raman peaks, monolayer MoS2 exhibits strain-and dopingdependent photoluminescence (PL) emission, offering an additional means to study the interaction between graphene and MoS2.…”
Section: Introductionmentioning
confidence: 99%
“…Use of supporting substrates facilitated its exploitability and prompted the development of the vast variety of graphene-based devices, such as field effect transistors 4 , transparent conducting electrodes 5 , gas and pressure sensors 6,7 , DNA single-molecule detectors, to name a few 8,9 . Although being widely adapted for the fabrication of current graphene-based devices and technologies, solid substrates largely affect graphene due to doping and induced strain, and thus hinder graphene's intrinsic properties [10][11][12][13][14][15][16][17][18] . The effect is even more prominent for CVD (chemical vapour deposition)-grown graphene samples, in which numerous inhomogeneities, inevitably caused by the growth and transfer processes, result in a wide variability in the band structure (and thus Raman signature) 12,13,15,16,[18][19][20][21][22][23] not only from sample to sample, but also from spot to spot within a single graphene sample.…”
mentioning
confidence: 99%
“…Although being widely adapted for the fabrication of current graphene-based devices and technologies, solid substrates largely affect graphene due to doping and induced strain, and thus hinder graphene's intrinsic properties [10][11][12][13][14][15][16][17][18] . The effect is even more prominent for CVD (chemical vapour deposition)-grown graphene samples, in which numerous inhomogeneities, inevitably caused by the growth and transfer processes, result in a wide variability in the band structure (and thus Raman signature) 12,13,15,16,[18][19][20][21][22][23] not only from sample to sample, but also from spot to spot within a single graphene sample. Here we study graphene supported by liquids, namely graphene at liquid/air and liquid/liquid interfaces, which provide well-defined interfacial boundaries, unlike solid/air interfaces.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that the substrate significantly affects the graphene layer 19,20 . The effects of the substrate may include doping 21 , strain 22 , and/or mixing of electronic states 23 . The easiest approach to study the effect of the substrate is a comparison of the behavior of single-layer graphene and turbostratic graphene bilayer on SiO 2 / Si substrate 24 .…”
mentioning
confidence: 99%